2015
DOI: 10.1089/apc.2014.0346
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to HIV Care and Treatment Among Participants in a Public Health HIV Care Relinkage Program

Abstract: Improving patient retention in HIV care and use of antiretroviral therapy (ART) are key steps to improving the HIV care continuum in the US. However, contemporary quantitative data on barriers to care and treatment from population-based samples of persons poorly engaged in care are sparse. We analyzed the prevalence of barriers to clinic visits, ART initiation, and ART continuation reported by 247 participants in a public health HIV care relinkage program in King County, WA. We identified participants using HI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
74
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(80 citation statements)
references
References 23 publications
4
74
1
1
Order By: Relevance
“…These reasons are consistent with those reported elsewhere in the literature 10,18,25. Encouragingly, many of these reasons are addressable through HIV care coordination and case management programming.…”
Section: Discussionsupporting
confidence: 90%
“…These reasons are consistent with those reported elsewhere in the literature 10,18,25. Encouragingly, many of these reasons are addressable through HIV care coordination and case management programming.…”
Section: Discussionsupporting
confidence: 90%
“…Tedaldi et al [7] noted that patients who were publicly insured were less likely to be retained in care. Dom-browski et al [23] also identified that cost (e.g. lack of insurance) was a significant barrier to them continuously accessing care despite, as the authors noted, the study being conducted in a US state with universal access to care.…”
Section: Resultsmentioning
confidence: 99%
“… NA, not applicable a King County cases excluded because investigation of those cases began >5 years prior to the surveillance period for this analysis and did not differentiate cases found to have evidence of care during the surveillance period from cases with evidence of care after the surveillance period 15 b Idaho cases were identified using clinic medical records instead of laboratory surveillance reports c Prevalent HIV cases in the jurisdiction at the time of identification of cases for investigation …”
Section: Tablementioning
confidence: 99%
“… a King County cases excluded because investigation of those cases began >5 years prior to the surveillance period for this analysis and did not differentiate cases found to have evidence of care during the surveillance period from cases with evidence of care after the surveillance period 15 …”
Section: Tablementioning
confidence: 99%